A Type-Aware Coding Approach to Joint Source-Channel Coding - Yao, Xinyuanmeng; Ma, Xiao (IEEE communications letters, 2021)
In this letter, we propose a type-aware coding approach to joint source-channel coding (JSCC) and present a concrete construction with polarization-adjusted convolutional (PAC) codes. A data sequence is first encoded by enumerative coding and then encoded by a data-dependent PAC code, resulting in a transmitted codeword. At the receiver, a type-search decoding algorithm is employed, and the implementation complexity can be reduced by searching only those typical types. Simulation results show that the presented JSCC scheme can outperform the conventional tandem coding scheme with a fixed-to-fixed-length source code and achieve a performance within the gap between the upper and lower bound on the minimum FER of finite-length JSCCs.